Barriers to healthy behavior from the perspective of the social determinants of health and disease - Pinzón Gómez, Daniel (2019)
The purpose of the present article is to make a critical analysis to the dominant classic epidemiological positionthat explains health-disease duality from genetics and lifestyles. It talks about how political, economic, cultural,environmental and demographic structure are strongly influenced by the social determinant of health, related tosanitary inequities, which may pose barriers to the adoption of healthy lifestyles, especially to people in extremepoverty, armed conflict, disasters and other hard conditions, which are prevailing circumstances in low andmiddle income countries. It discusses the need to transcend the paradigm of health education which is highlyprescriptive and does not offer the expected results. The research is documentary, and was based on a journalisticliterature review. It concludes that it is necessary to transcend into a holistic paradigm to explain the healthdisease process; it is also essential to work in the solution of the structural sanitary inequities to solve livingconditions that make people to persist in habits that carry bad health